1971
DOI: 10.1507/endocrj1954.18.91
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dopamine Implanted in the Median Eminence on the Estrous Cycle of the Rat

Abstract: SynopsisA mixture (DA-C) of dopamine hydrochloride and cholesterol in a ratio of 2 to 1 or 5 to 1 by weight was implanted into different hypothalamic regions of the rat and allowed to persist for more than two weeks. The estrous cycles and ovarian histology were examined to determine effects of the treatment. When the tip of the cannula containing DA-C (2 to 1) hit the posterior median eminence (ME) and a small part of the arcuate nucleus (AN), the rats showed prolonged estrus. The ovaries of these rats showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1973
1973
1999
1999

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…It seemed un likely that the infused agent could have remained in situ for more than a matter of hours, as would have been the case with the chronic dopa mine-cholesterol implants of Uemura and Kobayashi [1971], yet restoration of responsiveness to NE in some instances required several weeks. It appeared more likely that recovery involved some regenerative process such as that required to restore function to adrenergic nerve endings following treatment with 6-hydroxydopamine (6-OH-DA).…”
Section: Discussionmentioning
confidence: 99%
“…It seemed un likely that the infused agent could have remained in situ for more than a matter of hours, as would have been the case with the chronic dopa mine-cholesterol implants of Uemura and Kobayashi [1971], yet restoration of responsiveness to NE in some instances required several weeks. It appeared more likely that recovery involved some regenerative process such as that required to restore function to adrenergic nerve endings following treatment with 6-hydroxydopamine (6-OH-DA).…”
Section: Discussionmentioning
confidence: 99%
“…Other laboratories [1,8,II,18,22] as well as our own (6,7,9] have previously indicated an inhibitory role for DA in the regulation of LH secretion in rats. The response to DA has also been shown to depend on the steroid background in rats [9] and humans [13].…”
Section: Discussionmentioning
confidence: 69%
“…However, there are results which support the opposite hypothesis, namely that dopaminergic neurones exert an inhibitory effect upon gonadotrophin release (Fuxe et al 1969(Fuxe et al , 1972Ähren et al 1971). These studies, based largely on turnover studies and histofluorometric techniques, are supported by the findings of Uemura & Kobayashi (1971 ) who showed that dopamine implants in the medial basal hypothalamus inhibited ovulation and produced prolonged dioestrus. The results from the present study also show that high doses of dopamine are in themselves inhibitory (Table 1) and this would agree with the above hypothesis.…”
Section: Discussionmentioning
confidence: 70%